Financial Development, Efficiency and Competition of ASEAN Banking Market - Vimal Prakash Rao, A/L Subramaniam (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to examine the nexus between financial development, competition and efficiency of ASEAN countries over the period 2011 to 2016. Using dataset 78 banks over the ASEAN countries, the application of Data Envelopment Analysis (DEA) to measure efficiency, Herfindahl-Hirschman Index to measure market concentration, Lerner Index to measure market power. The dynamic panel approach namely Generalized Method of Moments (GMM) is employed to examine nexus between financial development, competition and efficiency of banks. The empirical results of nexus between financial development, competition and efficiency drawn three conclusions: firstly, competition is positively related to efficiency (technical efficiency and pure technical efficiency). Secondly, competition is negatively related to scale efficiency. Thirdly, financial development is negatively related to efficiency (pure technical efficiency) and competition. Nevertheless, GDP are positively related to competition. The results of this study imply encourage competition in banking sector foster the efficiency. Development in financial sector make banks inefficient and underutilized resources while improve market power.